Pulse Wave Velocity in Atherosclerosis - Kim, Hack-Lyoung; Kim, Sang-Hyun (Frontiers in Cardiovascular Medicine, 2019)
Early detection of subclinical atherosclerosis is important to reduce patients’ cardiovascular risk. However, current diagnostic strategy focusing on traditional risk factors or using risk scoring is not satisfactory. Noninvasive imaging tools also have limitations such as cost, time, radiation hazard, renal toxicity and requirement for specialized techniques or instruments. There is a close interaction between arterial stiffness and atherosclerosis. Increased luminal pressure and shear stress by arterial stiffening causes endothelial dysfunction, accelerates the formation of atheroma, and stimulates excessive collagen production and deposition in the arterial wall, leading to the progression of atherosclerosis. Pulse wave velocity (PWV), the most widely used measure of arterial stiffness, has emerged as a useful tool for the diagnosis and risk stratification of cardiovascular disease (CVD). The measurement of PWV is simple, noninvasive, and reproducible. There have been many clinical studies and meta-analyses showing the association between PWV and coronary/cerebral/carotid atherosclerosis. More importantly, longitudinal studies have shown that PWV is a significant risk factor for future CVD independent of well-known cardiovascular risk factors. The measurement of PWV may be a useful tool to select subjects at high risk of developing subclinical atherosclerosis or CVD especially in mass screening.